Does it matter what is trained? A randomized controlled trial evaluating the specificity of alpha/delta ratio neurofeedback in reducing tinnitus symptoms - Jensen, Martin; Garcia Alanis, Jose Carlos; Hüttenrauch, Eva; Winther-Jensen, Matilde; Chavanon, Mira Lynn; Andersson, Gerhard; Weise, Cornelia (Brain Communications, 2023)
Previous studies showed that alpha/delta ratio neurofeedback was effective in reducing unpleasant psychological, emotional and perceptual consequences of tinnitus. The main goal of the present study was to investigate, whether the specific combination of enhancing alpha frequency band activity and reducing delta frequency band activity was necessary, or merely sufficient, to obtain a positive treatment outcome regarding tinnitus distress and intensity. A second research aim was to assess the relative contribution of neurofeedback-related non-specific and general non-specific effects in neurofeedback treatment. In a three-arm, randomized controlled trial, 94 chronic tinnitus patients were randomly assigned to one of three conditions: alpha/delta ratio neurofeedback (n = 31), beta/theta ratio neurofeedback (n = 28) and non-neurofeedback minimal treatment intervention (n = 35). Neurofeedback participants underwent 10 treatment sessions over a 4-week period. Outcome measures were collected pre-, mid- and post-interventions and at 3-months follow-up. The Tinnitus Handicap Inventory and the Tinnitus Magnitude Index were used as primary outcome measures for tinnitus distress and tinnitus intensity. EEG data recorded during training supplemented primary outcomes. Since data were repeated measures, the analyses used a two-level mixed effects model approach including by-subject random effects (random intercept). For the Tinnitus Handicap Inventory, the results showed no interaction effect. For the Tinnitus Magnitude Index, the analysis showed a significant time × group interaction, indicating that both alpha/delta ratio neurofeedback and beta/theta ratio neurofeedback reported reduced tinnitus intensity. Analysis of EEG data showed a consistent pattern for the alpha/delta ratio over the course of training. Compared to beta/theta ratio neurofeedback, alpha/delta ratio neurofeedback showed an elevated response. Conversely, for the beta ratio to theta ratio, the pattern was more inconsistent, with no clear indication of superiority for beta/theta ratio neurofeedback over alpha/delta ratio neurofeedback. The main question of this piece of research was whether alpha/delta ratio neurofeedback demonstrated frequency band specificity in the alleviation of tinnitus distress and perceived intensity. Results showed that alpha/delta ratio neurofeedback was sufficient but importantly ‘not’ necessary to achieve a positive outcome on both the Tinnitus Handicap Inventory and Tinnitus Magnitude Index, when compared to beta/theta ratio neurofeedback. Still, the data suggest a trend towards specificity for alpha/delta ratio neurofeedback. Because of this, it may be too premature to discard alpha/delta ratio neurofeedback in the treatment of tinnitus. Recommendations for future studies are outlined.
CRIS-Team Scopus Importer:2024-03-27
Keywords: alpha; delta; EEG; neurofeedback; tinnitus